Application of an imputation method for variance estimation under pseudo-likelihood when missing data are NMAR. Issue 14 (18th July 2017) - Kwon, Amy M.; Tang, Gong
ABSTRACT: When data are outcome-dependent non response, pseudo-likelihood yields consistent regression coefficients without specifying the missing data mechanism. However, it is onerous to derive parameter estimators including their standard errors from the regression coefficients under pseudo-likelihood (PL). The present study applies an imputation method to compute the asymptotic standard errors of parameter estimators. The proposed method is simpler than Delta method and it showed similar effect size of the standard errors to bootstrapping in simulation and application studies.